Kewajiban Pemerintah dalam Pemenuhan Kuota Minimal 2% Pekerja Penyandang Disabilitas pada Lingkungan Pemerintah - Zora, Zimtya (Universitas Ekasakti, 2023)
The government must ensure that the implementation of the human rights of every citizen is guaranteed without discrimination. There are three obligations that must be fulfilled by the state in this regard, to protect, to promote and to fulfill. Persons with disabilities have the same rights and opportunities to get work in any field without any differences. International law and national law have stipulated the rights of people with disabilities, so there is no more discrimination against them.